E-152 Neurointervention in the pediatric population: 18-years' experience from a single center. (23rd July 2022) - Donnelly, B; Monteiro, A; Recker, M; Khawar, W; Waqas, M; Cappuzzo, J; Reynolds, R; Siddiqui, A; Levy, E
Abstract : Introduction: Neuroendovascular techniques often have to be adapted in pediatric patients due to their smaller and more fragile vasculature. Additionally, children can have more complex etiologies, given that cardiovascular comorbidities associated with cerebrovascular disease are not usually present at this age. In our institution, the pediatric hospital and endovascular department are closely linked allowing multidisciplinary management of pediatric patients in a timely manner. We report our center's cohort of pediatric neurointervention, aiming to contribute with insights from 18 years of experience. Methods: Retrospective review of our neuroendovascular database was performed. We included all patients 0–21-years-old who underwent neurointervention. Results: We included 114 patients, comprising 22 aneurysms, 41 AVMs, 19 tumors, 9 acute intracranial occlusions, dissections or stenosis, and 23 miscellaneous cerebral vascular disorders. The rate of periprocedural complications was 14.9%. Overall mortality was 2.6%. Details about each one of these diseases' treatment, recurrence, and outcomes are available on Tables 1 to 5 . Conclusions: At out institution, multidisciplinary interaction allowed the treatment of a wide variety of cerebrovascular diseases in the pediatric population. Pediatric patients carry high complication risks due to frequent presence of systemic conditions, but joined experience from pediatric neurology, neurosurgery and neurointervention departments allow their treatment with optimal planning and results. Disclosures: B. Donnelly: None. A. Monteiro: None. M. Recker: None. W. Khawar: None. M. Waqas: None. J. Cappuzzo: None. R. Reynolds: None. A. Siddiqui: 1; C; Co-investigator for NIH - 1R01EB030092–01, Project Title: High Speed Angiography at 1000 frames per second; Mentor for Brain Aneurysm Foundation Carol W. Harvey Chair of Research, Sharon Epperson Chai. 2; C; Amnis Therapeutics, Apellis Pharmaceuticals, Inc., Boston Scientific, Canon Medical Systems USA, Inc., Cardinal Health 200, LLC, Cerebrotech Medical Systems, Inc., Cerenovus, Cerevatech Medical, Inc.. 4; C; Adona Medical, Inc., Amnis Therapeutics, Bend IT Technologies, Ltd., BlinkTBI, Inc, Cerebrotech Medical Systems, Inc., Cerevatech Medical, Inc., Cognition Medical, CVAID Ltd., E8, Inc., Endostream M. 6; C; National PI/Steering Committees: Cerenovus EXCELLENT and ARISE II Trial; Medtronic SWIFT PRIME, VANTAGE, EMBOLISE and SWIFT DIRECT Trials; MicroVention FRED Trial & CONFIDENCE Study; MUSC POSITIVE Tri. E. Levy: 2; C; Claret Medical, GLG Consulting, Guidepoint Global, Imperial Care, Medtronic, Rebound, StimMed, Misionix, Mosiac, Clarion, IRRAS. 3; C; Medtronic. 4; C; NeXtGen Biologics, RAPID Medical, Claret Medical, Cognition Medical, Imperative Care, Rebound Therapeutics, StimMed, Three Rivers Medical.